JAIS 2022
DOI: 10.31526/jais.2022.240
|View full text |Cite
|
Sign up to set email alerts
|

Novel Muon Tomography Detector for the Pyramids

Abstract: Cosmic-ray muons which impinge upon the Earth's surface can be used to image the density of geological and man-made materials located above a muon detector. The detectors used for these measurements must be capable of determining the muon rate as a function of the angle of incidence. Applications of this capability include geological carbon storage, natural gas storage, enhanced oil recovery, compressed air storage, oil and gas production, tunnel detection, and detection of hidden rooms in man-made structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The new pyramid muon detector, described in more detail in [5], is made of two solid plates of EJ-200 scintillator [12], each of which have orthogonal grooves on either side of the plate containing BCF-92 wavelength shifting fibers (WLS) [13]. The simulation of each plate used two plates of half the total thickness.…”
Section: Simulation Of the Muon Detectormentioning
confidence: 99%
“…The new pyramid muon detector, described in more detail in [5], is made of two solid plates of EJ-200 scintillator [12], each of which have orthogonal grooves on either side of the plate containing BCF-92 wavelength shifting fibers (WLS) [13]. The simulation of each plate used two plates of half the total thickness.…”
Section: Simulation Of the Muon Detectormentioning
confidence: 99%
“…𝜇𝑁 𝐴𝑙 → 𝑒𝑁 𝐴𝑙 (20) Eq. ( 19) represents a radiative decay of μwith a mean lifetime of τμ ≅ 2.2 μsec.…”
Section: Geant4 Simulationsmentioning
confidence: 99%
“…Muons are one of the most versatile particles in both particle physics and nuclear engineering. Not only are muons the key particles in accelerator and neutrino studies, e.g., CMS and miniBooNE [1,2], but also a promising non-conventional radiographic probe in muon applications, e.g., nuclear reactor and waste imaging [3][4][5][6][7], homeland security [8][9][10][11][12][13][14], geotomography [15][16][17][18][19], and archeology [20,21]. In particle physics, two important quantities, muon trajectory and momentum, need to be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that MT has a wide range of applications, including the imaging of volcanoes [1,2], pyramids [3,4], hidden underground structures [5,6], nuclear reactors [7,8], high-Z materials [9], high-Z and medium-Z materials [10], and bedrock sculpting beneath an alpine glacier [11]. The imaging techniques used in MT are often based on plastic scintillators [12,13], emulsion [14], and gas [15] detectors.…”
Section: Introductionmentioning
confidence: 99%